Novel Design of LLC Resonant Converter with Peak Gain Adjustment - P. Kowstubha; K. Krishnaveni; K. Ramesh Reddy (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
The main advantages of a half-bridge LLC resonant DC/DC converter having two inductors (LL) and a single capacitor (C) compared to the other load resonant converters are its less amount of circulating currents and large bandwidth for Zero Voltage Switching (ZVS). It also has the advantage of limited tuning of operating frequency to get the regulated output when variable frequency control method is implemented on the converter. This DC/DC converter is widely used in server and telecom applications due its higher efficiency and reliability. In this paper, a novel design using peak gain adjustment is proposed for a LLC resonant DC/DC converter with a design example of 400V/12V-5A used in server based applications. For the specifications of the converter mentioned, an experimental set up is built and evaluated with the Texas instruments power switch FSFR 2100 IC in closed loop configuration. The experimental results proved an improved efficiency of 94% for the converter with the novel design proposed.